Characterising parameters in Gcn1 relevant for Gcn2 activation : this dissertation is submitted for the degree of Doctor of Philosophy, Biochemistry, Massey University, Auckland, New Zealand. EMBARGOED until 4 June 2029. - Gottfried, Susanne (Massey University, 2022)
The protein kinase Gcn2 ("General control non-depressible" 2) is present in virtually all eukaryotic cells assessed thus far, from yeast to humans. Gcn2 supports the cells to cope with nutrient deficiency. Upon amino acid starvation, Gcn2 phosphorylates the alpha subunit of eukaryotic translation factor (eIF2α), which subsequently stimulates the translation of the transcription factor Gcn4. Gcn4 then induces the expression of stress-response genes involved in amino acid biosynthesis. At the same time, intracellular protein synthesis is downregulated. Activation of Gcn2 requires the binding of uncharged tRNA to the HisRS-like domain, which depends on the physical interaction between Gcn2 and Gcn1. Formation of the Gcn1-Gcn2 complex involves direct binding of the N-terminal RWD domain in Gcn2 to the RWD binding domain (RWDBD) in Gcn1. Malfunction of Gcn2 is implicated in various diseases such as cancer and Alzheimer's. By hyper-activating Gcn2, cancer cells take advantage of Gcn2 to satisfy their high nutrition demand. Healthy cells do not critically depend on Gcn2, making Gcn2 a promising target for potential drug development. Understanding Gcn2 function in detail may help identify suitable targets that prevent or treat such diseases. The aim of the study was to gain a deeper understanding of properties in Gcn1 determining binding to Gcn2 and test whether targeting the protein-protein interaction between Gcn1-Gcn2 could be a suitable approach to inhibit Gcn2.--Shortened abstract
Embargoed until 4 June 2029
Keywords: Proteins; Carrier proteins; Protein-protein interactions; 340407 Proteins and peptides